Factors affecting workplace well-being : Building construction projects - Rani, Hafnidar A.; Radzi, Afiqah R.; Ahmad Rizal, Alias; Almutairi, Saud Jaza; Abdul Rahimi, Abdul Rahman (MDPI, 2022)
This study explores the factors affecting workplace well-being in building construction projects. The objectives of this study are (1) to investigate the critical factors for workplace well-being in building construction projects, (2) to compare the critical factors between large enterprises (LEs) and small-medium enterprises (SMEs), and (3) to compare the critical factors between high-rise building construction projects and non-high-rise building construction projects. Data from 21 semi-structured interviews with construction industry professionals in Malaysia and a systematic literature review were used to develop a potential list of factors. Then, the factors were used to create a survey that was distributed to industry professionals. Data from 205 valid responses were analyzed using mean score ranking, normalization, the Kruskal–Wallis test, and overlap analysis. Fourteen critical factors were determined, including salary package, working hours, project progress, planning of the project, workers’ welfare, relationship between top management and employees, timeline of salary payment, working environment, employee work monitoring, communication between workers, insurance for construction worker, general safety and health monitoring, collaboration between top management and employee, and project leadership. This study contributes to the body of knowledge by identifying the critical factors for improving workplace well-being. The study findings allow researchers and practitioners to develop strategies to promote workplace well-being in building construction projects.